The Comparative Analysis of the Postural Stability Assessment Methods - Kaupužs, Aivars; Lāriņš, Viesturs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The sense of balance is one of the most important functional capabilities that provide the postural position of the human body and the ability to move. Vestibular disorders are most commonly found in the elderly population, but this problem has not been adequately studied in children and teenagers. The digital force platforms and functional tests that can be carried out without the hardware are commonly used for postural balance assessment. The aim of the study is to compare EUROFIT balancing test and digital platforms BIOSWAY results. Eighty-three 11–14(M=12.5) year-olds primary schools pupils performed both balance tests. The research data reveals significant problems of postural stability, but results of both methods do not correlate (r=-0.14 to 0.2). The study results indicate the necessity to continue to develop and approve methods for early diagnosis of balance disorders in children that could be available and usable.